2000
DOI: 10.1200/jco.2000.18.18.3247
|View full text |Cite
|
Sign up to set email alerts
|

Phase I-II Study of Paclitaxel, Cisplatin, and Gemcitabine in Advanced Transitional-Cell Carcinoma of the Urothelium

Abstract: This combination of paclitaxel, cisplatin, and gemcitabine is feasible and highly active in patients with advanced TCC of the urothelium. Further evaluation of this regimen in patients with TCC is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(81 citation statements)
references
References 31 publications
5
75
0
1
Order By: Relevance
“…203 In phase 2 studies, paclitaxel has been shown to be effective both as a single agent and in combination with gemcitabine and/or cisplatin. [204][205][206] Poor renal function prohibits the use of cisplatin-based regimens, and thus, carboplatin was used with the intent of providing similar efficacy to cisplatin with less renal toxicity. 207 A study of the paclitaxel, carboplatin, and gemcitabine regimen was shown to have a high response rate and median survival of 14.7 months, making this regimen a potential alternative to cisplatin-based chemotherapy.…”
Section: Urinary Diversionmentioning
confidence: 99%
“…203 In phase 2 studies, paclitaxel has been shown to be effective both as a single agent and in combination with gemcitabine and/or cisplatin. [204][205][206] Poor renal function prohibits the use of cisplatin-based regimens, and thus, carboplatin was used with the intent of providing similar efficacy to cisplatin with less renal toxicity. 207 A study of the paclitaxel, carboplatin, and gemcitabine regimen was shown to have a high response rate and median survival of 14.7 months, making this regimen a potential alternative to cisplatin-based chemotherapy.…”
Section: Urinary Diversionmentioning
confidence: 99%
“…The combination of paclitaxel, gemcitabine and cisplatin (Bellmunt et al, 2000); the one with ifosfamide, paclitaxel and cisplatin (Bajorin et al, 1998); and one with paclitaxel, gemcitabine and carboplatin (Hussain et al, 2001) showed promising activity with predominantly haematological toxicity. The last study was comprised of patients with normal and poor renal function (Hussain et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In support of DNA methylation in small-cell bladder carcinoma PH Abbosh et al this theory, novel chemotherapy regimens, which include microtubule-targeting agents for TCC, are currently being explored and have shown promising results. 33,34 In addition, one case of a sustained response of SCBC to a paclitaxel-based regimen has been reported. 35 In our study, 86% of patients had methylation in at least one component of their bladder tumors.…”
Section: Discussionmentioning
confidence: 99%